Window tinting films for microwave absorption and terahertz applications - Bychanok, Dmitry S.; Padrez, Y.; Liubetski, N.; Arlouski, A.; Kushniarou, U.; Korobov, I.; Halimski, I.; Kulahava, T.; Demidenko, Marina; Urbanowicz, A.; Macutkevic, Jan; Kuzhir, Polina P. (Journal of applied physics)
We demonstrate that commercially available window tinting films could be used multifunctionally, i.e., for electromagnetic shielding and absorption at frequencies below 1 THz along with visible light and ultraviolet protection. The fine control of the film optical properties by their structural composition can also be used to extend their performance to the lower frequency ranges, i.e., terahertz and microwave. The electromagnetic properties of two types of thin protective films loaded with either carbon or iron oxide micro- and nano-inclusions were studied in microwave (12-18 GHz) and terahertz (0.2-1.0 THz) frequency ranges vs their inner structure. The reflection and transmission coefficients of studied tint films were investigated using waveguide and free space measurements and compared with theoretical modeling results. The effective sheet resistance was estimated from the experimental data.